2021
DOI: 10.1111/psyg.12675
|View full text |Cite
|
Sign up to set email alerts
|

Increased insulin resistance is associated with vascular cognitive impairment in Chinese patients with cerebral small vessel disease

Abstract: Background The aim of this study was to investigate the association between insulin resistance (IR) and vascular cognitive impairment (VCI) in patients with cerebral small vessel disease (CSVD). Methods A total of 275 CSVD patients were enrolled in this retrospective case–control study. The homeostatic model assessment of insulin resistance (HOMA‐IR) was used to measure the index of insulin resistance. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA). Spearman's correlation coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…When the hippocampus is damaged, the concentration level of NAA changes, which is significantly correlated with memory ability. [9][10][11] Research has shown that the volume of the hippocampus in dementia patients is significantly reduced compared to normal individuals. The normal volume of the hippocampus is basically between 2.00 and 3.57cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…When the hippocampus is damaged, the concentration level of NAA changes, which is significantly correlated with memory ability. [9][10][11] Research has shown that the volume of the hippocampus in dementia patients is significantly reduced compared to normal individuals. The normal volume of the hippocampus is basically between 2.00 and 3.57cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…У дорослих підвищена продукція TNFα у вісцеральній жировій тканині позитивно корелює зі ступенем ожиріння та інсулінорезистентністю [26,39,76]. Як у поперечних, так і в поздовжніх педіатричних дослідженнях TNF-α асоціюється з параметрами резистентності до інсуліну, МС і ступенем надмірної ваги [27,87].…”
Section: основні біохімічні маркери розвитку запаленняunclassified
“…IL-18 стимулюєвироблення гамма-інтерферону (IFN-γ), який, у свою чергу, ймовірно, причетний допатогенезу атеросклерозу. IL-18 є цитокіном, якийє предиктором метаболічного синдрому [17,25,31,76] TNFα є ще одним цитокіном, що виробляється в жировій тканині, в основному з локальних макрофагів, і його виробництво також змінюється пропорційно масі жирової тканини та корелює з резистентністю до інсуліну, обидва є основними ознаками MС [84]…”
Section: основні біохімічні маркери розвитку запаленняunclassified